Elementi critici e «casi-studio» della VIA delle infrastrutture viarie - Grazia Napoli (Aestimum, 2009)
The infrastructures in-form (or de-form) territorial systems, since they produce the structure which multiple interrelations are plotted on. The foundation of a consensual language dominion, which the social integration of environmental values is based on, can be obtained by going on with the epistemological renewal of the Science of evaluation (Rizzo 1972 e 1999). The EIA can harmonize environmental values with economic, ethic, aestetic, political and cultural values. The EIA analysis of two road-infrastructures (the Bridge on the straits of Messina and the railway Siracusa-Gela) pointed out that there is a communicative gap among political, juridical, administrative and estimative areas, and that there are also methodogical distortions, procedurals incohereance, epistemological incongruities and absence of rules.